BUSINESS PLAN PT. PANEL SURYA GAMA INFINITY DENGAN ANALISIS KELAYAKAN INVESTASI MENGGUNAKAN METODE PAYBACK PERIOD DAN BREAK EVEN POINT - Supono, Joko; Siti, Nurhifni Aida (Program Studi Teknik Industri Universitas Muhammadiyah Tangerang, 2025)
In designing a company, one of the most crucial aspects to consider is the increasing utilization of Renewable Energy, particularly Solar Energy, as a substitute for conventional electricity. Based on this aspect, the author aims to determine the extent of the business opportunity for the proposed company. The growth of Renewable Energy usage in Indonesia has reached 147.02% in terms of Solar Energy adoption, with the implementation and utilization of Solar Power Plants (PLTS) increasing by 200% during the period of 2020–2024. This study aims to analyze the investment feasibility and business planning projection for a new company, PT. Panel Surya Gama Infinity. The analysis is conducted based on several key aspects, including: industry and competitor analysis using the PESTEL method (Political, Economic, Social, Technological, Environment, and Legal), market and marketing analysis, development of organizational structure and human resources, operational planning, and financial feasibility analysis. Financial projections are analyzed for the period 2025 to 2029 through income statements, changes in equity, balance sheets, and cash flow reports. The results show a Payback Period of 1.81 years, a Break Even Point (BEP) of Rp 8.37 billion, a Contribution Margin of 59.6%, and a Return on Investment (ROI) of 47.11% in the second year. These indicators demonstrate strong business feasibility and effective capital utilization. The company is projected to reach break-even in the second year and is considered financially and strategically feasible to run. Keyword: Business Plan, PESTEL Analysis, Payback Period, Break Even Point, Return on Investment (ROI)